Формування та розвиток загальної теорії стійкості (середина XVIII ст. — 30-і рр. ХХ ст.) - Кілочицька, Т.В. (Наука та наукознавство, 2013)
У статті розглянуто історію вивчення стійкості (середина XVIII — початок XX ст., світовий контекст). Досліджено внесок А. Пуанкаре та О.М. Ляпунова в розвиток загальної теорії стійкості. Показано розвиток їх ідей у працях російських та українських учених. В статье рассмотрена история изучения устойчивости (середина XVIII — начало XX в., мировой контекст). Исследован вклад французского ученого А. Пуанкаре и русского ученого А.М. Ляпунова в развитие общей теории устойчивости. Показано дальнейшее развитие их идей в трудах русских и украинских ученых. The history of basic research in stability is given. Contributions from H.Poincaré, a French mathematician, mechanic and physicist, and O. Lapunov, a soviet mathematician and mechanic (working in the Kharkiv university) to development of the general theory of stability are shown. In 1892—1902, O. Lyapunov constructed an original robust mathematical apparatus to study stability of motion. Development of ideas and methods of H.Poincar of H.Poincar³e and O. Lapunov in works of later Ukrainian and Russian scientists is shown.